2006
DOI: 10.1088/0963-0252/15/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Study on the characteristics of ECR plasma spatial distribution

Abstract: The characteristics of the spatial distribution of electron cyclotron resonance (ECR) plasma in an ECR-plasma enhanced metalorganic chemical vapour deposition system with a divergent magnetic field are investigated by a single Langmuir probe. The results show that the spatial distribution in the resonance room has a significant density gradient in both radial and axial directions. The ECR plasma density attains its highest value, about 3.0 × 10 11 cm −3 , at a position that moves away from the ECR point in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…´at substrate level with an almost flat n r p ( ) behavior at approximately the same discharge pressure [59,60]. Both these results are similar to the results of Eddy et al, who found plasma densities at the substrate level between 2 10 10 ´cm −3 and 3 10 10 ´cm −3 (in Cl 2 /Ar mixtures, 500 W microwave power) [57].…”
Section: Langmuir Probe Measurementssupporting
confidence: 87%
“…´at substrate level with an almost flat n r p ( ) behavior at approximately the same discharge pressure [59,60]. Both these results are similar to the results of Eddy et al, who found plasma densities at the substrate level between 2 10 10 ´cm −3 and 3 10 10 ´cm −3 (in Cl 2 /Ar mixtures, 500 W microwave power) [57].…”
Section: Langmuir Probe Measurementssupporting
confidence: 87%
“…These typically operate on volume sources at pressures of 10 -3 to 10 -2 torr. Electron-cyclotron ion sources can operate at pressures of about 10 -3 torr [Xu 2008] and can achieve uniform plasmas [Fu 2006]. The ion density at the accelerator grids must be very uniform to produce multiple beamlets that are each well focused.…”
Section: Neutral Beam Injectorsmentioning
confidence: 99%
“…More details about this ECR-PECVD system and the spatial plasma density distribution in the system can be found in Refs. [12,13].…”
Section: The Process Of Gan Film Grown With Ecr-mopecvdmentioning
confidence: 99%